Cancer incidence among workers in the Norwegian ferroalloy industry. Issue 4 (April 1986) - Kjuus, H; Andersen, A; Langård, S; Knudsen, K E
Abstract : The total mortality and the incidence of cancer was studied among a cohort of employees at the six oldest ferrosilicon and ferromanganese plants in Norway. The cohort consisted of 6494 men employed for more than 18 months before 1970 and has been followed up from 1953 to 1982. The standardised incidence ratio (SIR) for cancer (all sites) was 0.94. The observed number of cancers was as expected for lung cancer (SIR = 0.99) and for most of the other cancer sites studied. A statistically significant reduction of stomach cancer was found (SIR = 0.72). There was an increased incidence of lung cancer (SIR = 1.75) and cancer of the prostate (SIR = 1.56) in the workers at one ferrosilicon plant and of colonic cancer (SIR = 1.90) at another ferrosilicon plant.